Knowledge Enhancement of Landless and Marginal Farmers through Entrepreneurship Training on Goat Farming (Indian Journal of Extension Education, 2023)
The study focused on assessing the cognitive effectiveness of entrepreneurial development training on goat rearing for landless and marginal farmers in Maharashtra’s Beed district carried out during 2020-21. A group of Twenty-five farmers were selected based on WhatsApp messages sent to registered KVK groups and a newspaper announcement. The training covered housing, disease management, improved goat breeding, feeding, feed preparation, and marketing intelligence. It was found that education level, socio-economic status, scientific interest, land ownership, social engagement, and marketing skills positively influenced knowledge acquisition. The trainee’s knowledge gained to the tune of 172 per cent more in seven days of training compared to the benchmark. Goat production and management including wildlife corridor preservation and promoting local vegetation through controlled grazing were key aspects. The study emphasized the importance of goat rearing training for farmers in the Beed district, showcasing substantial knowledge gains and identifying factors affecting participants’ learning outcomes.